The strategies of blended learning in new normal era at Kuala Lumpur Indonesian School - Hanik, Elya Umi; Afriyanti, Iis; Ruchyyah, Sayida; Afiyah, Uli Nur; Robi'attuladawiyah, Wardah Ayu (Prodi PGMI IAIN Salatiga, 2021)
During the COVID-19 pandemic, teachers are now very much required to choose appropriate and correct learning strategies so that the process can be maximum. Kuala Lumpur Indonesian School (SIKL) applies Blended Learning strategies for the new normal era. This study aims to discuss learning strategies, implementation of learning strategies, analysis of learning strategies in the Kuala Lumpur Indonesian School (SIKL) based on Blended Learning with the TPACK (Technological, Pedagogical, Content knowledge) approach in the new normal era. This research uses descriptive qualitative research and content analysis techniques. The collection techniques used are the opinion (interview), analysis, and documentation. The data analysis technique is carried out using the data collection stages, data analysis, and conclusions. The results of study 1) The education strategy at Kuala Lumpur Indonesian Schools is written on the syllabus and lesson plans (lesson planning design) made by the Kuala Lumpur Indonesian School teacher unit (SIKL). 2) Implementing the Blended learning strategy of the Kuala Lumpur Indonesian School (SIKL) in the New Normal era in one class is divided into 2, namely: the first is implemented at home through web / online-based technology. The second is learning processes are carried out face-to-face.